L’anthropologie du criminel en France - Renneville, Marc (Criminologie, 1994)
This article examines the birth and growth of criminal anthropology in France. French physicians and anthropologists took an interest in criminals and theorized their behaviors before the famous Italian positivist school. French theorizing in this area developped in the early beginnning of the XIXth century with the concept of Esquirol's "monomanie homicide" and phrenology, the later gaining wide acceptance under the July Monarchy. Paul Rroca, leader of anthropology in France, was interested incidentally in the pathology of crime but it is Lombroso's Uomo delin-quente, which through the reactions it provoked, led to the development of this type of studies in France. In opposition to Lombroso, the forensic physician Lacassagne created in Lyon in 1885 a review of criminal anthropology which will continue to appear until 1915. His school of "Milieu social", took a very different viewpoint from Durkheimian sociology. In fact, Lacassagne wasn't so far from Lombroso than he said, and his approach was also in a medical frame. Morel's theory of degeneration deserves mention for the importance it gained at the end of the century with Magnan, a psychiatrist who "regenerated" the concept of "monomanie homicide" in an "impulsion morbide".This presentation of the most important trends of criminal anthropology in France distinguishes two uses of the terms "criminal anthropology" and "criminology" in the past and today. An attempt is also made to unterstand how the medicalization of deviance was possible and it's historical conditions of emergence.